2015
DOI: 10.1186/s12881-015-0164-3
|View full text |Cite
|
Sign up to set email alerts
|

Deletion of REXO1L1 locus in a patient with malabsorption syndrome, growth retardation, and dysmorphic features: a novel recognizable microdeletion syndrome?

Abstract: BackgroundCopy number variations (CNVs) can contribute to genetic variation among individuals and/or have a significant influence in causing diseases. Many studies consider new CNVs’ effects on protein family evolution giving rise to gene duplicates or losses. “Unsuccessful” duplicates that remain in the genome as pseudogenes often exhibit functional roles. So, changes in gene and pseudogene number may contribute to development or act as susceptibility alleles of diseases.Case presentationWe report a de novo h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2016
2016
2017
2017

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 40 publications
0
7
0
Order By: Relevance
“…1 These simple~2:1 ratios suggest that the extreme high and low ends of the otherwise continuous REXO1L1 copy number distribution might be due to large reciprocal duplications and deletions of the REXO1L1 cluster that are cytogenetically visible as EVs (Supplementary Figure 2). As gains of RP11-96G1 were far more frequent than losses in the healthy populations analysed by Redon et al, 8 D'Apice et al 2 may have found a rare benign euchromatic deletion variant of 8q21.2 rather than a novel microdeletion. If not due to dosage, any possible effects of a deletion would require alternative mechanisms such as enhancer adoption by genes flanking the REXO1L1 cluster 7 or the release of other genes from epigenetic control.…”
Section: Microdeletion or Euchromatic Deletion Variant?mentioning
confidence: 82%
See 4 more Smart Citations
“…1 These simple~2:1 ratios suggest that the extreme high and low ends of the otherwise continuous REXO1L1 copy number distribution might be due to large reciprocal duplications and deletions of the REXO1L1 cluster that are cytogenetically visible as EVs (Supplementary Figure 2). As gains of RP11-96G1 were far more frequent than losses in the healthy populations analysed by Redon et al, 8 D'Apice et al 2 may have found a rare benign euchromatic deletion variant of 8q21.2 rather than a novel microdeletion. If not due to dosage, any possible effects of a deletion would require alternative mechanisms such as enhancer adoption by genes flanking the REXO1L1 cluster 7 or the release of other genes from epigenetic control.…”
Section: Microdeletion or Euchromatic Deletion Variant?mentioning
confidence: 82%
“…If the patient studied by D'Apice et al 2 had half the lowest observed diploid copy number of 97, the remaining copies on the homologous chromosome 8 would be expected to compensate for the loss of the cluster from the chromosome 8 carrying the deletion. Using the less accurate method of real-time quantitative PCR 7 with calibrator plasmids as controls, D'Apice et al 2 reported diploid copy numbers that were in an order of magnitude lower with 16-24 diploid copies in 60 controls and 8 in their deleted patient.…”
Section: Microdeletion or Euchromatic Deletion Variant?mentioning
confidence: 97%
See 3 more Smart Citations